2022
DOI: 10.3389/fonc.2022.877379
|View full text |Cite
|
Sign up to set email alerts
|

From Therapy Resistance to Targeted Therapies in Prostate Cancer

Abstract: Prostate cancer (PCa) is the second most common malignancy among men worldwide. Although early-stage disease is curable, advanced stage PCa is mostly incurable and eventually becomes resistant to standard therapeutic options. Different genetic and epigenetic alterations are associated with the development of therapy resistant PCa, with specific players being particularly involved in this process. Therefore, identification and targeting of these molecules with selective inhibitors might result in anti-tumoral e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 253 publications
1
11
0
Order By: Relevance
“…( Do and Webster, 2021 ). Unfortunately, the vast majority of PCa patients will develop acquired resistance to most of these therapeutic agents ( Moreira-Silva et al, 2022 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…( Do and Webster, 2021 ). Unfortunately, the vast majority of PCa patients will develop acquired resistance to most of these therapeutic agents ( Moreira-Silva et al, 2022 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Among men, prostate cancer is the second most common neoplasm in the world [ 51 , 52 ]. Surgery, radiotherapy, hormone therapy, chemotherapy, and immunotherapy are some of the main treatment modalities, but prostate cancer resistance to conventional therapies remains a significant problem despite the availability of these treatment options [ 77 , 78 , 79 ]. Numerous studies in recent years have revealed ways to improve the effectiveness of antineoplastic therapy, including the incorporation of drugs or natural compounds with multi-functional nanoparticles, aiming to increase the immune system’s ability to identify and attack malignant cells [ 79 , 80 , 81 ].…”
Section: Recent Progress In Niosomes As Delivery Systems In Cancer Th...mentioning
confidence: 99%
“…Ipatasertib is an Akt inhibitor that has been demonstrated to resensitize CRPC cells to antiandrogens when combined with enzalutamide, inducing apoptosis and leading to remarkable tumor cell growth inhibition, both in vitro and in vivo [ 132 , 133 ].…”
Section: Agents and Strategies To Resensitize Crpc To Antiandrogen Th...mentioning
confidence: 99%